Is Religion Associated with Entrepreneurial Activity? - Andrew Henley (Institute for the Study of Labor (IZA), 2014)
This paper provides a quantitative investigation of the strength of the potential relationship between entrepreneurial activity and religious affiliation. The relationship between religion and economic development has attracted recent attention. A positive association may indicate that religion raises the social acceptability of entrepreneurial activity, by inculcating incentives to accumulate wealth and acquire personal responsibility, as well as providing social capital and may be particularly effective where state governance systems are weak. Institutionalist perspectives suggest that religious institutions may support definition of property rights. Economic benefits flow through reduced transactions costs. This paper engages these discussions in order to present a preliminary empirical investigation of the relationships which may exist across national boundaries between religion and entrepreneurship. Definitions of entrepreneurship are taken from the Global Entrepreneurship Monitor (GEM) studies for 2011 and 2012, focusing on the individual rather than on the business venture. Recent data on religious affiliation across countries are used to construct various measures of religious activity and diversity. Preliminary findings suggest, in particular, a significant association between GEM indicators and evangelical-pentecostal-charismatic Christian affiliation. The strength of these associations is offset by state regulation of religion. These findings suggest that attention needs to be paid to the potentially important role that certain forms of religion might play is providing a supportive cultural environment for entrepreneurship. They also suggest that policy-makers may wish to pay closer attention to the potentially supportive role that certain religious organizations might play in new business formation.
Keywords: L26; M13; O43; Z12; 330; entrepreneurship; economic development; religion